THE ROLE OF PULP AND PAPER MILLS IN THE DEVELOPMENT OF URBAN PLANNING ON SAKHALIN IN THE KARAFUTO PERIOD - Portnyagina Antonina P.; Zadvernyuk Lyudmila V. (Architecton: Proceedings of Higher Education, 2022)
The article presents the results of a study on the role of Japanese industry and, in particular, the pulp and paper mills of the Karafuto period on settlement plans on the island of Sakhalin. An analysis is made of the development of Japanese industry and transport infrastructure on the island. The city-making and city-forming role of the pulp and paper mills has been studied. The spatial planning and design characteristics of the pulp and paper mills are identified.